When do Risky Choices Justify Inequality? (Diametros, 2017)
Luck egalitarianism is the view that inequalities are justified when and only when a particular condition is met. Recent years have seen considerable debate about the exact nature of the risky choices thought by luck egalitarians to justify inequality. All positions in the debate emphasise the importance of choice, but they differ in the precise details of how choice features in the inequality-justifying condition. The present paper argues for a novel view about the conditions under which risky choices should justify choice in a manner that uncovers ambiguity and flaws in existing positions. It rejects existing accounts and develops a new hypothetical choice based account of inequality-justifying risk.